2008
DOI: 10.1016/j.jcme.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of cervical radiculopathy in a woman after chiropractic manipulation

Abstract: Objective: To describe a case regarding a woman with 2-level cervical disk herniation with radicular symptoms conservatively treated with chiropractic care including high-velocity, lowamplitude (HVLA) manipulation with complete resolution of her symptoms. Clinical Features: A 40-year-old woman developed right finger paresthesia and neck pain. Results of electrodiagnostics were normal, but clinical examination revealed subtle findings of cervical radiculopathy. A subsequent magnetic resonance imaging revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…No direct evidence could be found in the literature showing the superiority of SCM in patients with CR compared with traction. Only 2 case reports, [ 26 , 27 ] 2 retrospective case series, [ 11 , 12 ] and an observation series of 8 patients [ 28 ] explored the efficacy of SCM therapy, but these previous studies have small sample sizes and there is neither randomization nor control. One of the retrospective case series observed that among patients undergoing spinal manipulation after cervical epidural injection, 50% significant improvement and 30% experienced temporary improvement, while 20% exhibited no change.…”
Section: Discussionmentioning
confidence: 99%
“…No direct evidence could be found in the literature showing the superiority of SCM in patients with CR compared with traction. Only 2 case reports, [ 26 , 27 ] 2 retrospective case series, [ 11 , 12 ] and an observation series of 8 patients [ 28 ] explored the efficacy of SCM therapy, but these previous studies have small sample sizes and there is neither randomization nor control. One of the retrospective case series observed that among patients undergoing spinal manipulation after cervical epidural injection, 50% significant improvement and 30% experienced temporary improvement, while 20% exhibited no change.…”
Section: Discussionmentioning
confidence: 99%
“…The technical purpose aims to increase the range of motion, consequently relieve pain by the vertebral repositioning. 6,7 Besides being effective in cervical pain complaints, vertebral repositioning is are also indicated in cases of radiculopathy. 1,[8][9][10][11][12][13] One of the manual therapy technique which promotes the mobilization of nerve roots and acts to test and treat the peripheral nervous system, is the neurodynamic mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…C6-7 is the most commonly af-fected level of cervical disc herniation followed by C5-6 5,6) . Patients with cervical radiculopathy complain of pain in the neck, shoulder, arm, or chest and weakness, numbness/ tingling, paresthesia, and radicular pain, depending on the root or roots involved, usually in a myotomal distribution 7) . The area of radiating pain related to cervical radiculopathy is usually distributed within a dermatome 8) .…”
Section: Introductionmentioning
confidence: 99%